PREPARING YOUNG LEADERS: ENHANCING LEADERSHIP, MANAGEMENT, AND COLLABORATIVE SKILLS IN SCHOOL EDUCATION - Xalikova Maxfuza (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The study delves into the significance of training leadership skills in young people, the pedagogical and institutional challenges associated with integrating management studies into school curricula as a formal subject, highlighting its potential impact on students’ leadership development and practical competencies. Fostering leadership, collaboration, critical thinking, personal growth, and effective time management skills in young individuals has become increasingly important, and plays a vital role in equipping them to deal with future challenges.